Study on the Effect of Day Length and Seasonal Variation on Haematological, Biochemical and Hormonal Traits of Indigenous Guinea Fowl (Numida meleagris) in Ghana - Korankye Okyere; Kagya-Agyemang James Kwame; Annor Serekye Yaw; Asabere-Ameyaw Akwasi; Kyere Gyeabour Clement; Afua Sarpong Asamoa-Bonsu (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
This study was conducted to investigate the effect of day length and season on haematological characteristics, biochemical and hormonal profiles of laying Guinea fowls (Numida meleagris). Four hens and 1 male were each subjected to 12 hours of light and 12 hours of darkness (12L: 12D), 14hours of light and 10 hours of darkness (14L: 10D), 16hours of light and 8 hours of darkness (16L: 8D) and 18hours of light and 6 hours of darkness (18L: 6D). Each group was replicated three times and reared in three seasons (Dry-December-March, Major rains-April-July and Minor rains-August-November) in a 3x4 factorial experiment. Data were analyzed using General Linear Model procedure of SAS. Significantly (p<0.05) higher Packed cell volume (PCV), lymphocytes and eosinophil, total serum protein and prolactin values were observed in 16L: 8D as 14L: 10D resulted in highest (p<0.05) neutrophil and albumin. PCV and Platelets were highest (p<0.05) in major rains whiles red blood cells and neutrophil were highest (p<0.05) in dry and minor rainy seasons, respectively. Total serum protein increased (p<0.05) from the dry season to minor rainy seasons. Oestrogen and luteinizing hormones were highest (p<0.05) in major rains and prolactin levels were higher (p<0.05) in minor rains and lowest in major rains. Interaction effect was not significant (p>0.05) in all parameters except prolactin. The findings of this study suggest that daylength of 14-16hrs and major rainy season in Ghana supports adequate haematological, biochemical and hormonal profiles of Guinea.